Measures taken in the context of the Covid-19 and discussed at the WTO Committee on agriculture - Campos, Adriana (Instituto Interamericano de Cooperación para la Agricultura, 2021)
The purpose of this chapter is to take an inventory and to present the main content of some of the trade-related communications and declarations that WTO member countries submitted to the WTO Committee on Agriculture in 2020 and 2021 as response to the current pandemic.